The purposes and objectives of socialistic modernization in Deng Xiaoping’s comprehension - Karabassova, A. B. (Journal of Oriental Studies, 2016)
in the article are considered the purposes and objectives of socialistic modernization in Deng Xiaoping’s comprehension.